Effects of grain size on plastic deformation in a β CuAlBe shape memory alloy - Montecinos Espinoza, Susana de Los Angeles (2014)
The effects of grain size on the deformation under compression of a β Cu–11.4Al–0.5Be (wt%) polycrystalline shape memory alloy were analyzed. As the maximum stress increases, major levels of pseudoelastic strain are obtained and the strain retained on unloading increases. The plot retained strain versus applied strain gives a unique curve that is independent of the grain size, with a pure pseudoelastic behavior up to around 3% of applied strain. The largest pseudoelastic strain possible to obtain increases as the grain size increases. Surpassed that strain, plastic deformation occurs and the macroscopic plastic stress follows a Hall–Petch type relation. In samples with plastic deformation the reverse martensitic transformation occurs in two stages, with a second high temperature calorimetric peak associated to the transformation of plastic deformed martensite.